A práxis educativa no contexto de grupos de discipulado na Igreja Comunidade da Graça - Souza, Marcelo José de (2008)
The text is a theoretical research that seeks to present the implications of educational praxis in the context of discipleship groups of the Community Church of Grace. The aim of the study is to analyze and identify discipleship as an educational function in the context of the Local Church. The approach to theological and ecclesiastical significance comes from the works of Dietrich Bonhoeffer and Karl Barth. The educational approach is grounded in the work of Thomas Groome. Thus, one establishes a theological and an educational perspective in front of the object of study. It aims to inform about the dialogue between discipleship theory and its practice in the local church. The theories for the theological significance of discipleship are presented, as well as a theory for its contextualization in the field of Christian education, seeking similarities and differences between these and the practice in the Church of Grace headquarters in São Paulo. The methodology used is the comparative, seeking to develop a dialogue between theory and practice, with the aim of highlighting reflections on this praxis. It is summarized that the practice of discipleship groups in the Grace Community Church has limitations, as well as contributions to the Christian educational praxis (AU).